Fear or greed? assessment on investors’ investment decisions in equity funds - Johari, Maimunah; Shafiai, Syahiru; Wan Ahmad, Wan Marhaini (2023)
This study explores investors' investment decision in equity funds by examining the relationship between the money flows of with the fund’s performance which may become evident of investors’ adherence to Buffett's contrarian philosophy of “Be fearful when others are greedy and greedy when others are fearful”. This study uses panel data analysis to investigate 74 Islamic and 150 conventional Malaysian domiciled equity funds from 2007 through 2019. The findings revealed that investors of Islamic funds in Malaysia letting go of poor-performing funds while chasing more best-performing funds, which is inconsistent with Buffet’s advice. Meanwhile, conventional funds investors are perceived to be more adherence to the advice. The data employed for this study only covers the pre covid era by purpose since the market during covid would render different scenario. The findings of this study shall explain the money flows into and out from equity funds in Malaysia; hence enable to track the investment pattern among Malaysian in unit trust. The study reveals decision making behaviours among unit trust investors where investors who invest in the Islamic funds was perceived to behave differently to those of conventional funds investors due to Shariah requirements imposed on Islamic funds.